How Diversity Effects on Employees#x2019; Performance at a Non-Profit Orgainsation (Global Journal of Management and Business Research, 2021)
Objective: This study aims to show the link between the diversity management and employees#x2019; performance, how this non-profit organization differs between local and international employees#x2019; packages and how this effects their employees#x2019; performance negatively. In this context, diversity management is defined as the systematic and planned commitment by the organizations to recruit, retain, reward and promote a mix of employees (Henry, O., Evans A., 2007).
Keywords: diversity; employee#x2019; s performance; international and local employees